Evaluating Electronic Evidence in Malaysian Civil Courts: Current Admissibility and Future Legal Directions - Mohamad Aniq Aiman Alias; Wan Abdul Fattah Wan Ismail; Ahmad Syukran Baharuddin; Hasnizam Hashim; Tuan Muhammad Faris Hamzi Tuan Ibrahim (USIM Press, 2025)
International Conference On Syariah, Law And Science 2024 (CFORSJ i-CONF 2024) 7 November 2024 - 30 November 2024 Editorial Team: Wan Abdul Fattah Wan Ismail, Lukman Abdul Mutalib, Zulfaqar Mamat, Aspalilah Alias, Hasnizam Hashim, Ahmad Syukran Baharuddin, Muhammad Aniq Aiman Alias, Tuan Mohd Faris Hamzi Tuan Ibrahim, Radin Ahmad Taufik Salikin Izzaddin, Ahmad Salman Mohd Yusof. Organized : Centre of Research for Fiqh Forensics and Judiciary (CFORSJ), Faculty of Syariah and Law, USIM